Barriers and facilitators to opioid agonist treatment (OAT) engagement among individuals released from federal incarceration into the community in Ontario, Canada - Cayley Russell; Michelle Pang; Frishta Nafeh; Shanna Farrell Macdonald; Dena Derkzen; Jürgen Rehm; Benedikt Fischer (International Journal of Qualitative Studies on Health & Well-Being, 2022)
Introduction Correctional populations with opioid use disorder experience increased health risks during community transition periods. Opioid Agonist Treatment (OAT) can reduce these risks, but retention is a key challenge. This study addresses a knowledge gap by describing facilitators and barriers to OAT engagement among federal correctional populations released into the community in Ontario, Canada. Methods This article describes results from a longitudinal mixed-methods study examining OAT transition experiences among thirty-five individuals released from federal incarceration in Ontario, Canada. Assessments were completed within one year of participants’ release. Data were thematically analyzed. Results The majority (77%) of participants remained engaged in OAT, however, 69% had their release suspended and 49% returned to custody. Key facilitators for OAT engagement included flexibility, positive staff rapport, and structure. Fragmented OAT transitions, financial OAT coverage, balancing reintegration requirements, logistical challenges, and inaccessibility of ‘take-home’ OAT medications were common barriers. Conclusions Post-incarceration transition periods are critical for OAT retention, yet individuals in Ontario experience barriers to OAT engagement that contribute to treatment disruptions and related risks such as relapse and/or re-incarceration. Additional measures to support community OAT transitions are required, including improved discharge planning, amendments to OAT and financial coverage policies, and an expansion of OAT options.